Study of Modeling of Large-Scale Atmospheric Circulation Using Mathematics (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:Type of turbulent isobaric surfaces in the geostrophic state of the environment. It has been proven that depending on the index of high air temperature at the equator in the geological state of the air, the isobaric surface has the state of an oblate or elongated geoid.Materials and Methods:As you know, the geostrophic state plays an extremely important role in the dynamics of the atmosphere. Analysis of the estimates of the quantities included in the equation of atmospheric dynamics (scale analysis) makes it possible to write the following expressions for the projections of the velocity of the geostrophic wind.Results:As a result, we get the accompanying image. When the temperature rise at the equator is positive, the isobaric surface is in the state of an elongated geoid, and the warm air moves clockwise in advection to the column, where there is a greatest adduct and the breeze velocity at the column is limited.Conclusion:Thus, from the above analysis of the geostrophic state of the atmosphere, it follows that the following situations are possible at the pole in the geostrophic state. The first situation: the isobaric surface at the pole has the shape of an oblate geoid, the pressure decreases in comparison with the static state - a global isobaric minimum takes place. The second situation: the isobaric surface has the shape of an elongated geoid, the pressure at the pole increases in comparison with the static state - a global maximum takes place.